PENGEMBANGAN KURIKULUM BERBASIS KITAB KUNING PADA MA’HAD ALY DI ACEH - Teuku Zulkhairi; Muzakir Muzakir (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This qualitative descriptive study aims to explain the system of developing a yellow book-based Islamic education curriculum organized by a typical Islamic boarding school, Ma'had Aly in Aceh Province. Data were collected through interviews, observation, and documentation, then analyzed descriptively. The results showed that the yellow book became the main focus in curriculum development. At the planning stage, the preparation of yellow book-based courses, then mastery of the yellow book is used as special skill for graduates. In the implementation process, the yellow book is used as the main reference for learning then learning is held using the Khataman system converted to the Semester Credit System (SKS). The learning method is varied, combining lecture models and the yellow book learning model in Islamic boarding schools. The stages of curriculum evaluation are carried out in various ways, including quizzes, midterms, memorization of the Koran and mastery of the yellow book, final semester exams, and writing of treatises.